Energy Dependent Laser Annealing of Au Thin Films On P-type Si for High-Performance Photodiode - binti Mahadzor, Nurul Amirah; Ahmad Hadi Ali, (Enhanced Knowledge in Sciences and Technology, 2024)
Achieving high ohmic contact efficiency of metal contacts on photodiode is quite challenging due to the low electrical contact  characteristics. In the context of photodiodes, ohmic contacts are crucial for efficient extraction of photocurrent generated by the device. In this study, Au thin film was deposited on a p-type silicon using DC sputtering technique followed by laser annealing treatment by using Nd:YAG laser at different energies. The samples were characterized based on the morphological, topological, electrical, and optical properties by using Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), Four-Point Probe and UV-Visible Spectroscopyrespectively. The result analysis of AFM shows that the highest laser energy, which is 55 mJ, has the highest grain size and surface roughnesscompared to the as-deposited sample. Next, the topological analysis of SEM shows that the annealed sample with energy of 55 mJ appeared to have more defects than the 35 mJ and as deposited samples. The electrical characterization analysis shows that the resistivity of the Au thin films dropped as the laser energy increases. The analysis of optical properties shows the sample annealed at 55 mJ has the highest absorbance which is 8.4 at wavelength of 600 nm. The results indicatethat the laser annealing could significantly improve the efficiency of Au thin films which can be potentially applied in photodiode devices.